Water budget, water use efficiency in agriculture in Olifants catchment - Rasiuba, Thabo Cecil (My University, 2009)
Eighty percent of the agricultural land worldwide is under rain-fed agriculture that takes place on most soils that are generally low in fertility with attendant high on farm water losses, thereby resulting in low crop yields. This is particularly significant in sub-Saharan African states where a higher percentage of the population is involved in agriculture and the economy is predominantly driven by rural-based rain-fed agriculture. In the Olifants catchment, the challenges in rainfed agriculture are compounded by erratic, highly variable rainfall patterns in space and time. The study area (Sekororo, B72A quaternary catchment) is within lower Olifants region. It is located between latitude 24000’00” and 24025’00” South and between longitude 30015’00” and 30045’00” East. The survey sites within the B72A quaternary catchment are Worcester, Enable, Ha-Fanie, and Sofaya. The results on soil nutrients indicate that the soil fertility is very poor, indicative of poor land management which also impacts adversely on water use and crop yields. The data from Statistics South Africa indicate that average number of people per household dwelling at B72A quaternary catchment is five. Taking into account maize consumption of 100kg per person per annum and average number of persons per household, maize required to achieve food security would be 500kg per household per annum and at current average crop yield of 300kg/ha, food insecurity is very high for rain-fed farmers. The data on rainfall partitioning indicate that at least 38% of the received rainfall is lost to run-off. The modeled results indicate that crop yield can be improved to 800kg/ha if significant portion of rainfall lost to run-off is harvested, thereby eliminating food insecurity for rain-fed farmers.